A bromopyrrole-containing diterpene alkaloid from the Okinawan marine sponge Agelas nakamurai activates the insulin pathway in Huh-7 human hepatoma cells by inhibiting protein tyrosine phosphatase 1B. Issue 10 (15th May 2017) - Yamazaki, Hiroyuki; Kanno, Syu-ichi; Abdjul, Delfly B.; Namikoshi, Michio
Graphical abstract: Abstract: Agelasine G (1 ), a known bromine-containing diterpene alkaloid, was isolated as a new type of protein tyrosine phosphatase (PTP) 1B inhibitor together with ageline B (2 ), an inactive debromo-derivative of1, from the marine sponge Agelas nakamurai collected at Iriomote Island in Okinawa, Japan. Further biological evaluations revealed that compound1 exhibited selective inhibitory activity against PTP1B over T-cell PTP and CD45 phosphatase. Compound1 also enhanced the insulin-stimulated phosphorylation levels of Akt in Huh-7 cells more strongly than compound2 . The results obtained in this study suggest that compound1 activates the insulin signaling pathway by inhibiting PTP1B activity.